Perencanaan Peningkatan Kualitas Pelayanan di AL Coffee Menggunakan Metode Service Quality dan Quality Function Deployment - Putra Arif Maulana; Deny Andesta (Universitas Islam Raden Rahmat, Malang, 2025)
AL Coffee is one of the hangout places for teenagers with a friendly concept, comfortable place, and affordable prices. Based on complaints, namely revenue in February to May 2024 is still fluctuating stable, suddenly in June to December 2024 and January 2025 there is a decline. To fix these problems, one of the methods used is the ServQual method as a measure of customer perceptions and expectations assisted by the GAP value if negative results will be made improvements, and QFD to translate needs with HOQ involving VOC. The results of ServQual and QFD obtained technical responses for improvement by conducting training for 1-2 months and involving experienced staff, using a digital queue number system to make orders more organized, routine checks and making a list of important facilities needed by customers, redesigning menu books with clear fonts, images, and detailed information, establishing a staff performance appraisal system and providing rewards for the best staff every month, making a list of all cafe equipment and checking at the beginning-end of work, and using a daily checklist so that cleaning is not missed.